Destiny vs. choice : the scientific and spiritual evidence behind fate and free will - Jones, Marie D., 1961- (Pompton Plains, NJ : New Page Books, 2011)
Since the day we are born, we are bombarded with the contradictory claims that our lives are predestined and that Fate deals us the cards we must play, or that our lives are the results of our choices and that we shape it as we go along.
Keywords: Fate and fatalism; Free will and determinism